PENGARUH KUALITAS INFORMASI DAN KUALITAS LAYANAN TERHADAP SIKAP DALAM PENGGUNAAN SISTEM APLIKASI DENGAN KEMUDAHAN PENGGUNAAN SEBAGAI VARIABEL INTERVENING PADA JASA TRANSPORTASI ONLINE (GOJEK) DI YOGYAKARTA: Studi Kasus pada Pengguna Jasa Transportasi Ojek Online Gojek di Yogyakarta - Putri Aprilia Isnaini; Ida Bagus Nyoman Udayana (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2019)
This writing is done to determine the effect of information quality and service quality on attitudes in the use of application systems with the ease of use of the system as an intervining variable in online transportation services (gojek) in Yogyakarta. The sample in this study is customers who use online motorcycle transportation services in Yogyakarta. The sampling technique uses accidental sampling technique. Data collection is done by distributing online questionnaires through the Goegle form and distributed with social media such as WhatsApp and Instagram on a 1-4 scale to measure 4 indicators. The results of this study show 1) the quality of information affects the ease of use, 2) the quality of service affects the ease of use, 3) the quality of information influences attitudes in use, 4) the quality of services does not affect attitudes in use, and 5) ease of use attitude in use.